KEMAMPUAN MEMBACA CEPAT MAHASISWA SEMESTER IV JURUSAN SASTRA INGGRIS FAKULTAS ILMU BUDAYA - Mangundap, Windy Amelia (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â  This skripsi is entitled â€œKemampuan Membaca Cepat Mahasiswa Semester IV Jurusan Sastra Inggris Fakultas Ilmu Budayaâ€. The objective of this research is to identify and analyze the speed reading ability of the fourth semester English students of the Faculty of Cultural Science. This research is based on the theory Brown (2007), Buzan (2001), and Clark (1967). The study is a quantitative approach. And data analysis focusing on quantitatif/statistical analaysis. The population of this research is English Department students in the Faculty of Cultural Science, and the sample is taken from the fourth semester students of the English Department as many as 26 students. The test are given in two categories: elementary level and intermediate level. The result of this research for the elementary level show that 4% of the students have the high test score, 61% of the students have the lowest score; the mean is 48,84, the median is 5, and the modus is 4. The results of this research for the intermediate level show that 4% of the students have the hightest score; 50% of the students have the lowest score, the mean is 51,53, the median is 5,5 and the modus is 6. It can be concluded the students perform better in intermediate level than the elementary level, but the speed reading of the fourth semester students of the English Department is less than satisfactory. Â  Keyworrds : Speed Reading. Â